6y+12+2y=5y-2

Simple and best practice solution for 6y+12+2y=5y-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+12+2y=5y-2 equation:


Simplifying
6y + 12 + 2y = 5y + -2

Reorder the terms:
12 + 6y + 2y = 5y + -2

Combine like terms: 6y + 2y = 8y
12 + 8y = 5y + -2

Reorder the terms:
12 + 8y = -2 + 5y

Solving
12 + 8y = -2 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
12 + 8y + -5y = -2 + 5y + -5y

Combine like terms: 8y + -5y = 3y
12 + 3y = -2 + 5y + -5y

Combine like terms: 5y + -5y = 0
12 + 3y = -2 + 0
12 + 3y = -2

Add '-12' to each side of the equation.
12 + -12 + 3y = -2 + -12

Combine like terms: 12 + -12 = 0
0 + 3y = -2 + -12
3y = -2 + -12

Combine like terms: -2 + -12 = -14
3y = -14

Divide each side by '3'.
y = -4.666666667

Simplifying
y = -4.666666667

See similar equations:

| 61=2x+17+x+17 | | 2n=10.06 | | 70=7x | | (2x-5)=-6 | | 9.5=v+2.8 | | 8x-6=3x+24 | | (2x-5)=6 | | 15x-8x=49 | | 12*c=108 | | 7y+8=-2y | | 2v+28=16+-4(v+7) | | -2(g+8)=64 | | -2-m=7 | | 4x^2=3x^2+9 | | 5(f-4)=-10 | | -5+5x=35 | | (x-2)=-2x-1 | | 8g-32=4g+16 | | X+17+4x=-29-4x-35 | | 1halfr+6=3-2r | | -10(s+3)=-71 | | (5x^3-6x^2+2x)+(-4x^2+3x)=42 | | 35x^2+76x+32= | | -10(s+3)=71 | | (x-5)=-6x-10 | | 3-2x^2=21 | | 10=-0.15x^2+3x | | t+10=7t+4 | | -8+3x=6+x | | 2-o=-42 | | (x-3)=-6x-17 | | -2+12=12 |

Equations solver categories